A Bánság változó szerepe Magyarország történeti térszerkezetében a 10-19. század között - Csüllög, Gábor (Közép-Európai Közlemények, 2010)
The spatial structure of the Hungarian historical statehood was complex, because the Hungarian Kingdom had developed function-spaces including defensive and impact spaces booth inside and outside the country in the Middle Ages. The process of regionalization, determinant in the construction of the country structure, was built on this regional operativity, with close interactions between these two elements of regionalism. Provinces representing larger areal connectivity units and smaller areal units connected to differentiated areal utilization and areal concentration were simultaneously present in the areal forms of administrative authority with various functions. In the 16th -17th century the Bánság was a part of the Ottoman Empire. After the Turkish’s expulsion the Habsburg Rule organized the defended frontier regions at the Ottoman borders. The Bánság became a mixing region of ethnic, cultural and economic influences from 17th century. The southern part of Hungary and the Bánság had a very important role in screening the effects of the Balkan.